Penyuluhan Cerdas Literasi Digital dalam Menghadapi Penyebaran Berita Hoaks pada Anggota Bhayangkari - Tri Romadloni, Nova; Supriyanti, Wiwit (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
The wide and rapid spread of hoax news via the internet, social media or other digital platforms has become a serious problem in society, including among Bhayangkari members. This community service has the goal of making digital literacy smart in helping Bhayangkari members deal with the spread of hoax news. This training aims to provide the understanding and skills needed to recognize, analyze, and respond wisely to hoax news. This counseling process is an experimental pretest-posttest given to Bhayangkari members. The results show that digital literacy smart counseling has a positive impact on increasing the knowledge and skills of Bhayangkari members in dealing with the spread of hoax news. This is about knowledge about hoax news, the ability to verify information, and awareness of the consequences of spreading hoax news. Bhayangkari members from the Jatiyoso branch who attended counseling were more skeptical of unverified information, were more careful in disseminating information, and were more active in checking the truth of news before believing it.